Penegakan Hukum Bagi Desk Collection Fintech Lending Ilegal yang Berimplikasi Tindak Pidana - Fidyah Faramita Utami; Andi Nurul Isnawidiawinarti Achmad (Universitas Batanghari Jambi, 2023)
The purpose of this study is to explain how law enforcement efforts are carried out by the Central Sulawesi Local Police against illegal fintech lending desk collections that use threats and/or defamation. Desk collection is a profession with the main tasks and functions of informing, reminding, and collecting customer obligations via telephone, but often unethical and uses threats to contact customers or other people who are not related to the customer because it can access all the data on the customer’s smartphone. This research is empirical juridical research using a socio-legal study approach. This study uses primary legal sources (interviews), secondary legal sources (books, articles in scientific journals, and other sources), and tertiary legal sources (materials obtained independently on the internet). The results of this study explain that law enforcement in cases of threats and/or defamation carried out by illegal fintech lending desk collection in the jurisdiction of the Central Sulawesi Local Police is inefficient due to hindering factors, both internally and externally. This is what causes cases of threats and/or defamation by illegal fintech lending to become increasingly widespread and are like a chain that never ends.